Insecurity and its implication for sustainable development in Nigeria: The role of religion - Ngwoke, Peace N. (HTS teologiese studies, 2022)
Nigeria’s high rate of insecurity has reached a stage where people’s safety is no longer guaranteed. This article examines the extent to which the current high rate of insecurity in Nigeria has affected sustainable development in the country. The increasing insecurity situation is now in a state where kidnapping has become the norm, and destruction of lives and property has become a daily reoccurrence, affecting all efforts to achieve sustainable development in Nigeria. This article aims to reflect on some of the recent cases of insecurity in Nigeria to ascertain the major implication of these insecurities on education, religion and the economy, and seeks ways to curb the insecurity menace in Nigeria. It is also indicated that religion has been used to incite the perpetrator’s action as various terrorist groups misinterpret the religious texts to justify their actions. The article concludes by arguing that religion can provide the needed coherence and social control needed to fight insecurity in Nigeria jointly, and once the difference in diversity is handled through cohesion and the social control function of religion, all stakeholders will be able to unite and fight insecurity off from the society. It therefore recommends that religious leaders should form the minds of Nigerians with the true contextual meaning of the religious text used to instigate insecurity.Contribution: This article highlighted the major implications of insecurity on education, poverty and the economy, which have greatly affected development in Nigeria. The article brings to light a theological reflection of the role religion can play in providing the coherence and social control needed to jointly fight insecurity in Nigeria. This work would greatly benefit religious bodies, government, civil society and students.